2017
DOI: 10.1007/978-3-319-55780-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Hepatorenal Tyrosinemia in Mexico: A Call to Action

Abstract: Hepatorenal tyrosinemia is a treatable metabolic disease characterized by progressive liver failure, renal damage and pronounced coagulopathy. Its clinical diagnosis is difficult because of its low prevalence and heterogeneous symptoms. In developed countries, expanded newborn screening, based on succinylacetone quantification by tandem mass spectrometry, has been very valuable in the early detection of hepatorenal tyrosinemia, providing the opportunity for rapid treatment of affected patients. In developing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The rate is significantly higher than in pre-nitisinone reports ( 8) but comparable to the reported 6-year survival rate of HT1 in Mexico (60%) (16). With nitisinone therapy, higher rates of 85% and 100% are reported in the Turkish and French series, respectively (21,29), transient interruption of the treatment due to lack of health insurance coverage is common in developing countries (17). Several studies have shown that nitisinone interruption can lead to higher mortality rate in HT1 by HCC (20), in addition to triggering neurological crisis (30), rapid deterioration (31,32) and death.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The rate is significantly higher than in pre-nitisinone reports ( 8) but comparable to the reported 6-year survival rate of HT1 in Mexico (60%) (16). With nitisinone therapy, higher rates of 85% and 100% are reported in the Turkish and French series, respectively (21,29), transient interruption of the treatment due to lack of health insurance coverage is common in developing countries (17). Several studies have shown that nitisinone interruption can lead to higher mortality rate in HT1 by HCC (20), in addition to triggering neurological crisis (30), rapid deterioration (31,32) and death.…”
Section: Discussionsupporting
confidence: 60%
“…Few reports on the outcome of HT1 from Arab countries are available, mainly from Egypt (12), Saudi Arabia (13), Tunisia (14), and Sudan (15). Furthermore, some developing countries, like Mexico (16,17), still struggle to diagnose early HT1 patients and offer them nitisinone, an expensive lifelong medical therapy. The aim of this study is to report the diagnostic and therapeutic challenges of a series of HT1 patients and their outcome over a 12-year-period, in a tertiary care center in Lebanon.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a small percentage of infants was diagnosed with tyrosinemia, a treatable metabolic disease with heterogeneous symptoms including progressive liver failure, renal damage and pronounced coagulopathy. Today, expanded newborn screening, based on succinylacetone quantification has been very valuable in the early detection of hepatorenal tyrosinemia, providing the opportunity for rapid treatment of affected patients (17). This report highlighted the importance of neonatal screening for detecting treatable causes of IC.…”
Section: Discussionmentioning
confidence: 95%
“…In this study group, we also found that 7/10 older siblings had a diagnostic odyssey, and they were frequently misdiagnosed with unspecified motor and intellectual disability (Table 3). This situation is common in low-income countries and has been described for several IEMs [35][36][37]. Thus, training physicians in IEMs and in neurodevelopmental skills is imperative in order to favor early detection of patients and to prevent or ameliorate health damage.…”
Section: Discussionmentioning
confidence: 99%